(untitled) (Biological Sciences - PJSIR, 2000)
Five toluene tolerant species were isolated from the activated sludge of a wastewater treatment plant (Dublin). The isolate were investigated for influence of pH on the growth in toluene. Four of the bacteria have been identified as Pseudomonas puiida and one as an Aeromonas caviae. When these bacteria were grown with toluene as the sole source of carbon and energy, the pH of the culture medium became acidic and dropped. 0.5 M sodium phosphate buffer was selected to investigate the optimum pH for growth in the presence of 500 IIIof toluene. In general, the growth was optimum between pH 5.8 and 7.4.